2000
DOI: 10.1159/000022168
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Strength and Mass of Lower Extremities in Relation to Functional Abilities in Elderly Adults

Abstract: Background: Functional and physiological declines in advancing age may be significant limiting factors in reduced physical activity. Sarcopenia of aging, as a normative process or disease, cannot entirely explain reduced physical activity in the elderly. Objective: The purpose of the study was to investigate the relationship between muscle loss and reduction in functional abilities in elderly adults and also to determine whether an exercise program can improve functional performance and muscle quality. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
6

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 31 publications
2
42
0
6
Order By: Relevance
“…It seems to indicate that accelerating aging seen in the ID group might be indirectly reflected by body composition values. Age-associated loss of muscle mass, sarcopenia [27], with concomitant loss of strength and decreased joint flexibility and mobility, contribute to frailty in the older adults and expose these individuals to increased risk [28,29,30,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…It seems to indicate that accelerating aging seen in the ID group might be indirectly reflected by body composition values. Age-associated loss of muscle mass, sarcopenia [27], with concomitant loss of strength and decreased joint flexibility and mobility, contribute to frailty in the older adults and expose these individuals to increased risk [28,29,30,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, numerous studies have demonstrated that resistance training is an effective measure to counteract sarcopenia in both healthy and frail older adults (Carmeli et al 2000;Charette et al 1991;Ferri et al 2003;Frontera et al 1988Frontera et al , 2000Frontera et al , 2003. It would appear that with an appropriate and effective exercise regimen, older adults may expect gains of 5-10% muscle CSA, accompanied by increases of 20-100% or more in muscle strength, depending on the muscle group under investigation.…”
Section: Muscle Size and Strength Changesmentioning
confidence: 99%
“…O TR isolado demonstrou ser relevante para a função de idosos (90% dos estudos) 23,[28][29][30][31][32][34][35][36] , sobretudo por seu decorrente ganho de força e mobilidade. O TR a longo prazo demonstrou ser desnecessário para ganhos funcionais.…”
Section: Funcionalidadeunclassified
“…Cerca de 65% dessa população tem alguma sensação de perda de equilíbrio 20 . Os efeitos de diferentes tipos de exercícios sobre equilíbrio e função são alvo de diversos estudos [21][22][23][24][25][26] , mas sem um desfecho concludente sobre muitos aspectos.…”
Section: Introductionunclassified